Total oxidation of naphthalene with zirconia-supported cobalt, copper and nickel catalysts - Leguizamón Aparicio, María Silvia del Valle (2017)
ZrO2 nH2O (hydrogel) impregnated with transition metals (Cu, Co, and Ni) was studied in this work as a precursor for the synthesis of CuO/ZrO2 (CuZ), CoOx/ZrO2 (CoZ), and NiO/ZrO2 (NiZ) catalysts, employed in the naphthalene oxidation reaction. Fresh and catalytically used materials were characterized by different physicochemical techniques, to compare the bulk and surface behavior, with particular attention to the effect of the supported metal species’ properties on the catalytic activity. Techniques such as X-ray diffraction (XRD), temperature programmed reduction (TPR), differential scanning calorimetry (DSC), Brunauer-Emmett-Teller (BET) surface area analyzer, diffuse reflectance spectroscopy (DRS UV-vis), and Raman spectroscopy, allow for establishing structural and textural aspects of the support, as well as the surface coordination and the accessibility of supported species. Results were in agreement with the CuZ > CoZ > NiZ sequence for the activity in naphthalene oxidation reaction. Electronic properties, ionic sizes, oxide phase deposition on the support surface, reducibility, metal-support interaction, and local site symmetry of metals seem to be decisive factors for the catalytic interaction with the gaseous phase.